Inhibition of Hyaluronic Acid Synthesis Suppresses Angiogenesis in Developing Endometriotic Lesions - Olivares, Carla Noemi (2016)
Background: The development and long-term survival of endometriotic lesions is crucially dependent on an adequate vascularization. Hyaluronic acid (HA) through its receptor CD44 has been described to be involved in the process of angiogenesis. Objective: To study the effect of HA synthesis inhibition using non-toxic doses of 4-methylumbelliferone (4-MU) on endometriosis-related angiogenesis. Materials and Methods: The cytotoxicity of different in vitro doses of 4-MU on endothelial cells was firstly tested by means of a lactate dehydrogenase assay. The anti-angiogenic action of non-cytotoxic doses of 4-MU was then assessed by a rat aortic ring assay. In addition, endometriotic lesions were induced in dorsal skinfold chambers of female BALB/c mice, which were daily treated with an intraperitoneal injection of 0.9% NaCl (vehicle group; n = 6), 20mg/kg 4-MU (n = 8) or 80mg/kg 4-MU (n = 7) throughout an observation period of 14 days. The effect of 4-MU on their vascularization, survival and growth were studied by intravital fluorescence microscopy, histology and immunohistochemistry. Main Results: Non-cytotoxic doses of 4-MU effectively inhibited vascular sprout formation in the rat aortic ring assay. Endometriotic lesions in dorsal skinfold chambers of 4-MU-treated mice dosedependently exhibited a significantly smaller vascularized area and lower functional microvessel density when compared to vehicle-treated controls. Histological analyses revealed a downregulation of HA expression in 4-MU-treated lesions. This was associated with a reduced density of CD31-positive microvessels within the lesions. In contrast, numbers of PCNA-positive proliferating and cleaved caspase-3-positive apoptotic cells did not differ between 4-MU-treated and control lesions. Conclusions: The present study demonstrates for the first time that targeting the synthesis of HA suppresses angiogenesis in developing endometriotic lesions. Further studies have to clarify now whether in the future this anti-angiogenic effect can be used beneficially for the treatment of endometriosis.